Digital and Legacy Telecommunications Efficiency in Indonesia: Evidence from a Two-Stage DEA - Eka Budiandri; Dadan Rahadian; Sora Baltasar; Sri Retnaning Sampurnaningsih (Greenation Research & Yayasan Global Resarch National, 2026)
This study examines operational efficiency of Indonesian telecommunications firms by distinguishing digital and legacy services within a two-stage framework, addressing whether efficiency differences arise from managerial performance rather than firm size amid digital transformation. Audited annual reports of three major operators from 2014 to 2024 are analysed. The first stage applies output-oriented Data Envelopment Analysis under Variable Returns to Scale to measure technical efficiency in converting operational inputs into heterogeneous revenue outputs. The second stage employs panel regression estimated using weighted EGLS with Cross Section SUR to explain efficiency variations through firm-level profitability indicators. Results reveal pronounced heterogeneity across firms. PT Telkomsel consistently achieves the highest VRS efficiency, reflecting superior managerial control independent of scale advantages. Input slack analysis identifies operational expenditure as the primary source of inefficiency, whereas labour input remains near optimal utilization and total assets show structural rigidity. Second-stage estimation indicates that Return on Equity positively and significantly affects efficiency, while Net Profit Margin lacks a significant individual effect, though profitability indicators are jointly meaningful. Sustainable efficiency improvement depends on strategic resource allocation, effective equity utilization, and disciplined cost management rather than scale expansion. This study contributes by integrating digital and legacy outputs within a two-stage DEA framework and linking operational efficiency to financial performance, offering actionable insights for managers seeking to enhance firm-level performance during digital transformation.